A influência da marca mutante no reconhecimento de marca país: “la respuesta es colombia” - Minto, Amanda Valladares de Andrade (2023)
The work aims to verify if the mutant brand has influence for the recognition of the Colombian brand La Respuesta es Colombia, launched in 2013, for its Colombian residents and Brazilians foreigners. Therefore, the theoretical background references used as a theorical research base are presented understanding the concept of brands and brands for places, country image, country identity, place branding, dynamic identities and mutant brand. Then, a compilation is carried out on the use of mutant brands as a creative tool for country brands and the understanding of the academic field productions that addresses the two themes. After approaching the use of mutant brands for countries, the Colombian development history of brand creation is elaborated also as transition from its previous brand, Colombia es Pasión, to the current one, as well as its conceptual characteristics and mutant structures. To verify the brand recognition, a total of 24 in-depth interviews were carried out, considering 12 people for the Brazilian sample and 12 people for the Colombian sample. The content analysis used the Atlas.TI software as a tool to organize and categorize the results according to each group of correspondents, being able to identify positive and negative aspects of the mutant brands as an instrument to build image recognition. From the results, it was possible to improve suggestions and strategic parameters for the creation of mutant brands.